Pentingnya Pengetahuan Pemeriksaan Payudara Sendiri sebagai Deteksi Dini Kanker Payudara - Supriyatiningsih, Supriyatiningsih; Rachmanio, Nicko; Kurniawan, Muhammad (Universitas Muhammadiyah Yogyakarta, 2022)
Breast cancer is included in the five types of cancer that result in death. The reason is the delay in early detection so that survivors of this type of cancer are generally detected at an advanced stage. The community service entitled